The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1111/pan.13466
|View full text |Cite
|
Sign up to set email alerts
|

Progress to publication of survey research presented at anesthesiology society meetings

Abstract: While abstract presentation facilitates rapid dissemination of survey research findings, the impact and utility of such studies may be limited until a full manuscript is published. In our review, 25% of abstracts presenting survey data at major anesthesiology meetings were eventually published. Larger sample sizes and a target population of patients or caregivers increased the likelihood of survey research being published in full form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…To assess other project characteristics predicting publication, the research team focused on objective measures that were likely to be reported in the limited space of a conference abstract (eg, the number of cases). 13 Anticipating missing data on key elements of project methods, the team did not evaluate scientific quality of projects based on a checklist such as Standards for Quality Improvement Reporting Excellence (SQUIRE). 6 The total number of cases analyzed was counted over the implementation period to reflect the scope of project implementation rather than the analysis of baseline data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess other project characteristics predicting publication, the research team focused on objective measures that were likely to be reported in the limited space of a conference abstract (eg, the number of cases). 13 Anticipating missing data on key elements of project methods, the team did not evaluate scientific quality of projects based on a checklist such as Standards for Quality Improvement Reporting Excellence (SQUIRE). 6 The total number of cases analyzed was counted over the implementation period to reflect the scope of project implementation rather than the analysis of baseline data.…”
Section: Methodsmentioning
confidence: 99%
“…Publication outcomes were ascertained in June 2019 using a predetermined search strategy in PubMed and Google Scholar, 13 previously used to track progress to publication of abstracts reporting original survey research. First, the PubMed database was searched using the abstract title, then using the names of the first and last authors, with keywords from the abstract title or text.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Nevertheless, by the 1960s, the scientific value of peer review was becoming widely accepted, and in recent years, publication in a peer-reviewed journal has become a standard metric of scientific productivity (for the researchers) and validity (for the study). [56] In fact, publication in peer-reviewed quality journals is used to evaluate the quality of research during the academic promotion process. Today, peer review continues to evolve with the introduction of open review (reviewer comments posted publicly with the final article), postpublication review (reviews solicited from readers in an open forum after article publication), and journal review networks (where reviews are transferred from one journal to another when an article is rejected).…”
Section: The History Of Scientific Peer Reviewmentioning
confidence: 99%
“…4 It is tempting to assume the differences in positive and negative trial results are simply the result of astute clinicians investigating interventions they know work; however, studies looking at abstract publications from meetings and trial registries do not support this hypothesis, and negative trials are going unpublished. 5,6 The causes of publication bias are numerous, and addressing them adequately has been a slow and methodical process. There has been concern that this bias is driven by editorial boards and journal editors trying to keep citation indexes and downloaded content as high as possible.…”
mentioning
confidence: 99%